PERAN TEORI DALAM STUDI KOMUNIKASI - Heriyadi Heriyadi (Universitas Islam Negeri (UIN) Mataram, 2018)
Communication-based on theory is very important, role theory helps get understanding and organize experiences. In theory, there are positions that play an important role in extracting information so that interpretations, judgments, and statements can be carried out easily. In addition, to reveal one's assumptions and characteristics, symbols and others cannot rely on a single perception, but must give rise to categories in a particular field that are determined by diverse space, time and types of scientific communication, including the theory of political communication , theory of interpersonal communication, intrapersonal communication theory, cultural communication theory, mass communication theory, and other theories of communication. The union between theory and communication must be in detail because in communication it is never separated from symptoms, phenomena, interactions and others that require interpretation. Thus the presence of theory in the realm of communication studies provides new colours and broader knowledge of the science of communication itself.